Mampu Bentuk Briket Variasi Bahan Briket Dengan Komposisi Perekat Serta Waktu Pencelupan Minyak Jelantah - Mohammad Nurhilal (Politeknik Negeri Jember, 2018)
AbstractIndonesia is given Â with abundant natural wealth which is capable of being transformed into source of energy. However, the utilization of these natural resources can not yet be optimized. An alternative solution to make fuel is briquette fuel. The general purpose of this research is to make briquettes of rice husk and garlic skin. While the specific purpose of this research is to know the result of briquette variation of adhesive material and briquette material with adhesive as well as time of reused oil dipping. The method of this research is experiment approach. The results showed that starch glue can be used as briquettes of rice husk and garlic skin; mixed variations of 60%, 70% and 80% starch glue blends were able to form briquettes; variations of pulp mixture 20%, 30% and 40% and without mixing the pulp can form briquettes; and the variation of briquette dyeing time of 1, 3, and 5 minutes had no effect on briquette solidity.Â Keywords: Briquette, rice husk charcoal, garlic skin charcoal, adhesive, solidity.